Task dependency of movement regulation in female gymnastic vaulting - Heinen, T.; Artmann, I.; Brinker, A.; Nicolaus, M. (Baltic Journal of Health and Physical Activity, 2015)
Background: In gymnastics vaulting it is thought that gymnasts regulate their run-up on the basis of visually perceived environmental information, such as the position of the springboard, with the aim of an accurate foot placement on the springboard. The question, however, arises if these regulative processes found in gymnastics vaulting can be generalized to other tasks with similar demands but differing dynamics?